2014
DOI: 10.1063/1.4859495
|View full text |Cite
|
Sign up to set email alerts
|

Design and initial results from a kilojoule level dense plasma focus with hollow anode and cylindrically symmetric gas puff

Abstract: We have designed and built a Dense Plasma Focus (DPF) Z-pinch device using a kJ-level capacitor bank and a hollow anode, and fueled by a cylindrically symmetric gas puff. Using this device, we have measured peak deuteron beam energies of up to 400 keV at 0.8 kJ capacitor bank energy and pinch lengths of ∼6 mm, indicating accelerating fields greater than 50 MV/m. Neutron yields of on the order of 10(7) per shot were measured during deuterium operation. The cylindrical gas puff system permitted simultaneous oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…Deuteron beam energy > 400 keV has been measured from time-of-flight measurements [9]. We have also observed that the optimum pressure for producing energetic deuteron beams is lower than the optimum pressure for maximum neutron yields in the LLNL device.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Deuteron beam energy > 400 keV has been measured from time-of-flight measurements [9]. We have also observed that the optimum pressure for producing energetic deuteron beams is lower than the optimum pressure for maximum neutron yields in the LLNL device.…”
Section: Resultsmentioning
confidence: 89%
“…The device, the neutron diagnostics, the ion beam diagnostic, and the diagnostic calibration details are described in detail in Ref. 9. The data shown for the neutron scaling law comparisons and ion beam measurements were collected using a 2 cm diameter copper anode, hollowed out to a depth of 0.6 cm with an inner diameter of 1.3 cm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LLNL dense plasma focus is a table top kJ-scale device 1 . The neutron yield in the experiment is measured with He3-based detectors.…”
Section: The Llnl Dense Plasma Focusmentioning
confidence: 99%
“…In particular, we are interested in whether the gradients set up inside a DPF could be used to accelerate an injected beam. Here we report on our first set of experiments injecting a 4 MeV deuteron probe beam into a 4 kJ (maximum) DPF [2] during the pinch phase. We also report results from supporting kinetic simulations [3], which predict the spatial and energy distribution of beam that has passed through the pinch region.…”
Section: Introductionmentioning
confidence: 99%